Well‐being of nursing staff on specialized units for older patients with combined care needs. Issue 2 (5th February 2018) - Collet, J.; de Vugt, M. E.; Schols, J. M. G. A.; Engelen, G. J. J. A.; Winkens, B.; Verhey, F. R. J.
Accessible summary: What is already known about the subject: Working in long‐term care is seen as a stressful, physically and mentally demanding occupation, and thus, nursing staff are at risk for work and stress‐related diseases. In older patients, psychiatric illnesses often occur in combination with physical illnesses, requiring nursing care that is specific to these combined care needs. The impact of caring for these patients on the mental well‐being of nurses is unknown. What this paper adds to existing knowledge: Nursing staff working on specialized units for patients with combined care needs experience high levels of self‐efficacy in combination with strong feelings of self‐rated competence. Although levels of burnout are relatively low, mental healthcare nursing staff is more at risk for burnout when working in specialized settings for patients with combined care needs than nursing home staff working in specialized settings for these patients. Nursing staff characteristics, such as years of working experience and age, seem more important in relation to staff well‐being than patient characteristics in specialized settings for combined care needs. What are the implications for practice: Staff well‐being might benefit from specializing care, so that patients with similar care needs are placed together and care is focused. The presence of specialized care units for older patients with combined care needs can allow for both targeted and focused allocation of nursing staff to these units and provision of specific training. Abstract: Introduction: In older patients, psychiatric illnesses frequently exist in tandem with physical illnesses, requiring nursing care that is specific to these combined care needs. The impact of caring for these patients on the mental well‐being of nursing staff is unknown. Aim: To investigate whether care characteristics of patients with combined care needs are related to the mental well‐being of nursing staff. Method: Well‐being of nursing staff was studied within a larger exploratory observational cross‐sectional study that examined the differences and similarities of specialized combined care units in Dutch mental healthcare and nursing home settings. Results: Nursing staff across settings, with more than 5 years of work experience, felt competent in caring for patients with combined care needs. No significant effects of care characteristics of patients with combined care needs on the work‐related well‐being of nursing staff were shown. Both mental health nursing staff and older employees, however, were found to be more at risk for burnout. Implications/Conclusion: Staff well‐being might benefit from placing patients with combined care needs together, so care is focused. The presence of specialized care units can allow for both targeted and focused allocation of nursing staff to these units and provision of specific training.